The nonlinearity properties of pulse signal of pregnancy in the three trimesters. (January 2023) - Li, Nan; Yu, Jiarui; Mao, Xiaobo; Zhao, Yuping; Huang, Luqi
Abstract: The purpose of this work sought to investigate the underlying activity state and dynamics characteristic changes of pulse in the three trimesters from healthy pregnant subjects by using nonlinear methods. Firstly, 176 healthy young pregnant women of different gestational ages were allocated for the study. The subjects were divided into three trimesters, namely first trimester, second trimester and third trimester, according to gestational age (8–12 weeks; 24–28 weeks; 32–36 weeks). Secondly, methods of nonlinear time series analysis, including phase-space reconstruction, time delay embedding, recurrence plot (RP), recurrence quantification analysis (RQA), Poincaré section and largest Lyapunov exponent (LLE) were applied to pulse time series to identify the unique characteristics of the pulse as a dynamical system. Finally, the natural complexity of pulse dynamics has been analyzed and assessed. The results demonstrated that (a) the predictability and regularity (DET: 97.499 v s . 98.471 v s . 98.319, p < 0 . 05 ), stability (LMAX: 5874.167 v s . 9311.667 v s . 5733.833, p < 0 . 05 ) and laminar states (LAM: 97.216 v s . 98.224 v s . 97.967, p < 0 . 05 ) of three trimesters are significantly; (b) the long-term changes of pregnancy pulse in second trimester is significantly higher compared with the first and third trimesters (SD2: 1.0697 v s . 1.0747 v s . 1.0075, p < 0 . 05 ); (c) the ability of subjects to respond to external stimuli gradually increases ( λ : 0.752 v s . 0.768 v s . 0.782, p < 0 . 05 ). The result of these analyses validates nonlinear characteristics of pulse with different gestation periods, while presence of significant difference has also been noticed. Additionally, the nonlinear methods are used to characterize the pulse changes during pregnancy from both qualitative and quantitative perspectives, which reveal important characteristics of biological signals. This gives us a good theoretical basis for the analysis and applied studies in Traditional Chinese Medicine(TCM). Highlights: The nonlinear methods are used to analyze the pulse of pregnancy in three trimesters. Reconstructed the dynamic behaviors of pregnancy pulse. Quantitatively and qualitatively characterize the internal attributes of pregnancy pulse. The experiments give the significant differences of pregnancy pulse characteristics.